Closed House Chicken Barn Climate Control Using Fuzzy Inference System - Kamis, M.S.; Abdullah, A.H.; Sudin, S.; Shukor, S.A.A.; Bakar, M.A.A.; Mustafa, M.H. (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2018)
The hazardous gases in chicken barn such as Ammonia (NH3) and hydrogen sulfide (H2S) are the health threats to the farm animals and workers which influenced by climate changes. The chicken barn requires real-time control to maintain the barn climate and monitor hazardous gases. The outdated on-off and proportional control are not so efficient in energy saving and productivity. The solution to monitor environment of the chicken barn is using wireless electronic nose (e-nose) and Short Messaging System (SMS). The e-nose system is used for the barn’s temperature and humidity data acquisition. The chicken barn climate control is utilizing fuzzy interface system. MATLAB software was used for the model which is developed based on Mamdani fuzzy interface system. The membership functions of fuzzy were generated, as well as the simulation and analysis of the climate control system. Results show that the performance of the fuzzy method can improve the system to control the barn’s climate. This system also provides real-time alerts to farmers based on specific limit value for the climate. It makes it easier for farmers to follow up on-site or remotely control the environmental conditions in the barn by using the SMS system.